EFFECTS OF CHRONIC REM SLEEP RESTRICTION ON ANXIETY-LIKE BEHAVIOR AND THE IMMUNE SYSTEM OF RATS - Fernandes, Eduardo Vignoto; Filgueiras, Guilherme Bracarense; Estanislau, Celio; Venancio, Emerson José (SaBios-Revista de Saúde e Biologia, 2020)
The objective of this study was to investigate the effects of partial chronic rapid-eye-movement (REM) sleep restriction (SR) (18 hours daily, 21 days) on anxiety-like behavior and the immune system in rats. Male Wistar rats were randomly allocated to sleep-restricted (n=14) and control (n=14) groups. During the experiment, the rats were immunized twice with chicken immunoglobulin Y (days 01 and 15). Blood samples were collected on days 01, 08, and 22, and the levels of antibodies (IgM, IgG1, and IgG2a) were measured. On day 22, the animals were tested in the elevated plus-maze (EPM). The results showed that sleep restriction increased adrenal weight and decreased body and spleen mass in rats. No changes in thymus weight were observed. Behavior in the EPM and antibody production were not altered by sleep restriction. Thus, one can infer that SR influenced the energy metabolism and spleen mass but does not interfere in antibody production and in the behavioral parameters of the animals investigated in the present study. EFEITOS DA RESTRIÇÃO CRÔNICA DE SONO REM SOBRE O COMPORTAMENTO ANSIOSO E O SISTEMA IMUNE DE RATOS O objetivo deste estudo foi investigar os efeitos da restrição parcial crônica do sono (RS) de movimento rápido dos olhos (REM) (18 horas/dia, por 21 dias) sobre o comportamento ansioso e o sistema imune em ratos. Ratos machos Wistar foram alocados aleatoriamente em grupos RS (n = 14) e controle (n = 14). Durante o experimento, os ratos foram imunizados duas vezes com imunoglobulina Y de galinha (dias 01 e 15). Amostras de sangue foram coletadas nos dias 01, 08 e 22, e os níveis de anticorpos (IgM, IgG1 e IgG2a) foram mensurados. No dia 22, os animais foram testados no labirinto em cruz elevado (LCE). Os resultados mostraram que a restrição do sono aumentou o peso da glândula adrenal e diminuiu a massa corporal e a massa do baço dos ratos. Nenhuma alteração no peso do timo foi observada. O comportamento ansioso avaliado pelo LCE e produção de anticorpos não foram alterados pela restrição do sono. Assim, podemos inferir que a RS influenciou o metabolismo energético e a massa do baço, mas não interferiu na produção de anticorpos e nos parâmetros comportamentais dos animais investigados no presente estudo.